2017
DOI: 10.1016/j.biopsych.2015.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Novel Dopamine Therapeutics for Cognitive Deficits in Schizophrenia

Abstract: Schizophrenia is characterized by profound cognitive deficits that are not alleviated by currently available medications. Many of these cognitive deficits involve dysfunction of the newly evolved, dorsolateral prefrontal cortex (dlPFC). The brains of patients with schizophrenia show evidence of dlPFC pyramidal cell dendritic atrophy, likely reductions in cortical dopamine (DA), and possible changes in DA D1 receptors (D1R). It has been appreciated for decades that optimal levels of DA are essential for dlPFC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
110
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(117 citation statements)
references
References 130 publications
0
110
0
3
Order By: Relevance
“…The drop-off in LMA at higher doses is typically caused by competition from hyperactivity, with intense stereotyped behaviors such as repetitive grooming (Arnsten et al, 2016) that are incompatible with translational movement. As expected, bell-shaped curves were seen in the hD1 mice with the three D1 agonists, A-77636, SKF 82958, and dihydrexidine (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drop-off in LMA at higher doses is typically caused by competition from hyperactivity, with intense stereotyped behaviors such as repetitive grooming (Arnsten et al, 2016) that are incompatible with translational movement. As expected, bell-shaped curves were seen in the hD1 mice with the three D1 agonists, A-77636, SKF 82958, and dihydrexidine (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Original research papers (Bruns and Fergus, 1990; Malherbe et al, 2008) and reviews (Christopoulos and Kenakin, 2002; May and Christopoulos, 2003; Epping-Jordan et al, 2007; Arnsten et al, 2016) have emphasized the predicted therapeutic advantages of allosteric potentiators. By amplifying the effectiveness of physiologic circuits, potentiators should give a needed boost to a hypoactive system while allowing the normal feedback loops to remain in control.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study of schizotypal personality disorder indicated that the D 1 receptor agonist dihydrexidine improved working memory (Rosell et al, 2015). However, the poor pharmacokinetic characteristics (reviewed by Arnsten et al, 2017) and the known cardiovascular effects of D 1 receptor agonists (e.g. severe hypotension) limit their clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive deficits are now considered a core feature of schizophrenia; 90% of patients with schizophrenia have deficits in ≥1 cognitive domain, including working memory (WM), attention, processing speed, reasoning and problem solving, social cognition, visual learning and memory, and verbal learning and memory (Table 1) (2,3). In addition, though cognitive symptoms are more predictive of functional outcomes, such as maintaining employment, current pharmacotherapy for schizophrenia focusing on dopamine D 2 receptor antagonism primarily addresses positive (psychotic) symptoms of the illness while leaving cognitive symptoms virtually untouched (2).…”
mentioning
confidence: 99%
“…In this issue of Biological Psychiatry , Arnsten et al thoroughly chronicle the research efforts to find a drug that improves cognitive deficits in schizophrenia via the D 1 R (3). Roadblocks have included drugs with poor blood-brain barrier penetration, nonselectivity for D 1 R, partial instead of full agonism, poor oral bioavailability, short duration of action, rapid tolerance, or intolerable side effects.…”
mentioning
confidence: 99%